THINKING OF 'ALI 'ABD AL-RAZIQ ON ISLAM AND THE COUNTRY - Dahrun Sajadi (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2023)
Muslim thinkers differ on whether or not Islamic teachings exist regarding the state or matters relating to Islamic politics. Two terms are closely related to this, namely Khilafah and imamate. Although taken from the same source, namely the Qur'an, thinkers reacted differently to the political praxis that developed in the Islamic world. Like the thoughts echoed by Ali Abdul Razik. This article applies a qualitative method. Furthermore, as a source of data based on library research, the works of Ali Abdul Razik are used as a reference. Moreover, the work of other Muslim thinkers is used as a comparison to developing this article. The basis for the difference in the thinking of 'Ali 'Abd al-Raziq with other 'ulama' lies in the unified understanding of whether or not the apostolic function of the Prophet Muhammad SAW was in terms of handling human relations vertically with Allah SWT and human relations horizontally with humans and with nature and its contents. His thought that the function of the Prophet Muhammad SAW was only as a religious leader supports the function of Islam as the religion of Rahmatan Lil Alamin, which must be spread worldwide. If the Prophet Muhammad SAW, apart from being a religious leader, was also the leader of the State of Medina, then the religion he brought was only for the State of Medina, and maybe the city of Makkah was added after the migration. It turns out that during and after his death until now, Islam has been preached by Muslims all over the world. The understanding of 'Ali 'Abd al-Raziq is considered to make a dichotomy between religious affairs and state affairs; in fact, this thought liberates the obligations of future Islamic leaders who cannot carry out both religious and state leaders. If the dual function of leadership becomes mandatory, then most leaders will violate the obligation because they cannot carry out their leadership. Meanwhile, the argument for obliging leadership to have dual functions simultaneously is not found either directly or figuratively. If religion and state affairs are separated, then religious affairs can be run without state affairs, and state affairs without religious affairs can also work. Conversely, suppose religious and state affairs must be united. In that case, religious affairs cannot be carried out without state affairs, and state affairs cannot be carried out without religious affairs. It means that Islam is obligatory in Islamic countries, and Islamic countries are obligatory on the Islamic religion. Many countries are running and developing without taking care of the Islamic religion, and Islam is developing in countries that do not take care of religion. Para pemikir muslim berbeda pendapat mengenai ada atau tidaknya ajaran Islam tentang negara atau hal-hal yang berkaitan dengan politik Islam. Ada dua istilah yang berkaitan erat dengan hal ini, yaitu khilafah dan imamah. Meskipun diambil dari sumber yang sama, yaitu Al-Qur’an, tapi dalam praksis politik yang berkembang di dalam dunia Islam tetapi para pemikir minyikapinya secara berbeda. Seperti pemikiran yang digaungkan oleh Ali Abdul Razik. Artikel ini menerapkan metode kualitatif. Dan sebagai sumber data yang berbasis kepada riset kepustakaan karya-karya Ali Abdul Razik dijadikan acuan. Dan karya pemikir muslim lainnya dijadikan pembanding untuk mengembangkan artikel ini. Dasar perbedaan pemikiran ‘Ali ‘Abd al-Raziq dengan ‘ulama’ lain terletak pada pemahaman bersatu atau tidaknya fungsi kerasulan Nabi Muhammad SAW dalam hal menangani hubungan manusia secara vertikal dengan Allah SWT dan hubungan manusia secara horizontal dengan manusia serta dengan alam dan isinya. Pemikiran beliau bahwa fungsi Nabi Muhammad SAW hanya sebagai pemimpin keagamaan mendukung fungsi Islam sebagai agama Rahmatan Lil Alamin yang wajib disebarkan ke seluruh penjuru dunia. Jika Nabi Muhammad SAW selain sebagai pemimpin agama juga sebagai pemimpin Negara Madinah, maka agama yang dibawanya hanya untuk Negara Madinah, dan mungkin ditambah kota Makkah setelah hijrah. Ternyata semasa dan setelah wafatnya beliau sampai sekarang agama Islam didakwahkan oleh umat Islam ke seluruh dunia. Pemahaman ‘Ali ‘Abd al-Raziq dianggap mendikotomikan urusan agama dan urusan negara, sebenarnya, pemikiran itu membebaskan kewajiban pemimpin Islam di kemudian hari yang tidak mampu mengemban sebagai pemimpin agama sekaligus sebagai pemimpin negara. Jika dwi fungsi kepemimpinan menjadi wajib, maka mayoritas pemimpin akan melanggar kewajiban karena tidak mampu menjalankan kepemimpinannya. Sedangkan dalil untuk mewajibkan kepemimpinan dwi fungsi itu sekaligus tidak ditemukan baik secara langsung maupun secara kias. Bahwa jika urusan agama dan negara dipisahkan, maka urusan agama dapat dijalankan tanpa urusan negara dan urusan negara tanpa urusan agama juga dapat berjalan. Sebaliknya, jika urusan agama dan negara wajib disatukan, maka urusan agama tidak dapat dijalankan tanpa urusan negara, dan urusan negara tidak dapat dijalankan tanpa urusan agama. Artinya agama Islam wajib di negara Islam, dan negara Islam wajib pada agama Islam. Ternyata, banyak Negara yang berjalan dan berkembang tanpa mengurus agama Islam, dan agama Islam berkembang di negara yang tidak mengurus agama.